Characterization of high-density mapping in catheter ablation for persistent atrial fibrillation: results from the Advisor™ HD Grid Mapping Catheter Observational study - Fiedler, Lukas; Roca, Ivo; Lorgat, Faizel; Lacotte, Jérôme; Haqqani, Haris; Jesser, Emily; Williams, Christopher; Roithinger, Franz Xaver; Steven, Daniel (Journal of interventional cardiac electrophysiology, 2023)
Background We quantified and characterized the outcomes of ablation in persistent atrial fibrillation (PersAF) subjects, and the utility of electroanatomical mapping with a market-released high-density (HD) mapping catheter. Methods PersAF subjects received electroanatomical mapping with the Advisor™ HD Grid mapping catheter, Sensor Enabled™ (HD Grid) and radiofrequency (RF) ablation to gather data regarding ablation strategies, mapping efficiency, quality, and outcomes. Subjects were enrolled from January 2019 to April 2020 across 25 international sites and followed for 12 months after the procedure. Results Three hundred thirty-four PersAF subjects (average age 64.2 years; 76% male; 25.4% previous AF ablation) were enrolled. Multiple map types were generated in a variety of rhythms using HD Grid. Significant differences in low voltage areas were identified in maps generated with the HD Wave Solution™ electrode configuration when compared to the standard configuration, which in some cases, influenced physicians’ ablation strategies. PV-only ablation strategy was used in 59.0% of subjects and 34.1% of subjects received PV ablation and additional lesions. Of the subjects, 82.0% were free from recurrent atrial arrhythmias at 12 months and new or increased dose of class I/III antiarrhythmic drugs. About 6.0% of subjects experienced a serious adverse event or serious adverse device effect through 12 months including 1 event deemed related to HD Grid and the index procedure by the investigator and 1 death unrelated to study devices. Conclusions The results of this study (NCT03733392) support the safety and utility of electroanatomical mapping with HD Grid in subjects with complex arrhythmias, such as PersAF in the real-world setting.